2011
DOI: 10.1111/j.1365-2958.2011.07850.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and complementation of the selenocysteine biosynthesis pathway reveals a hierarchy of selenoprotein gene expression in the archaeon Methanococcus maripaludis

Abstract: :selenocysteine synthase with the corresponding genes from M. maripaludis S2 restored the mutant's ability to synthesize selenoproteins. However, only partial restoration of the wild-type selenoproteome was observed as only selenocysteine-containing formate dehydrogenase was synthesized. Quantification of transcripts showed that disrupting the pathway of selenocysteine synthesis leads to downregulation of selenoprotein gene expression, concomitant with upregulation of a selenium-independent backup system, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…In contrast, both Ffd variants in Mc. maripaludis are selenoproteins (266); hence, the organism requires the presence of selenium to grow on formate (267,268). Genetic dissection has demonstrated that each homolog confers a competitive growth advantage, with single mutants impaired and double mutants unviable for formatotrophic growth (242).…”
Section: Ffd: F 420 -Reducing Formate Dehydrogenasementioning
confidence: 99%
“…In contrast, both Ffd variants in Mc. maripaludis are selenoproteins (266); hence, the organism requires the presence of selenium to grow on formate (267,268). Genetic dissection has demonstrated that each homolog confers a competitive growth advantage, with single mutants impaired and double mutants unviable for formatotrophic growth (242).…”
Section: Ffd: F 420 -Reducing Formate Dehydrogenasementioning
confidence: 99%
“…The mutant strains had the same genotypes as reported previously for the selC, pstK, and spcS mutations in the wild type [22] and were, thus, verified. With H 2 +CO 2 as the energy source the …”
Section: Construction and Phenotypic Analysis Of A M Maripaludis Jj mentioning
confidence: 94%
“…M. maripaludis strain JJ [20], for which no genome sequence is available, encodes, like strain S2, two sec-containing Fdhs, Fdh1 and Fdh2, but no selenium-independent isoform. While in M. maripaludis JJ fdhA2 is barely expressed under laboratory conditions and cannot complement an inactivated fdhA1 gene [21], fdhA1 is expressed at a high level regardless if the organism grows on H 2 +CO 2 or formate [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations